SEJARAH PENDIDIKAN ISLAM DI MALAYSIA - Wiro Riwansah; Eli Ernawati (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The aim and purpose of education in Islam is among others to form a cohesive Muslim personal in the development of spiritual, physical, emotional, intellectual and social. It is not only produced good citizens but also covers the formation of a complete human capital in terms of religious and worldly life. In addition, the education that is based on the teachings of Islam also aimed at producing righteous human that can meet the needs of the world and life in the hereafter. The main focus of this journal is about the history and development of Islamic Education subject in Malaysia. It also includes the etymology of education and the Islamic education debate from the views of scholars and academics. Discussions also focused on the development of Islamic education subject in Malaysia in the early period of Islam, development during the Western colonization and development of education in Islam after the country gained independence.